The Scale of Quantitative Assessment Adherence to Treatment «QAA-25»: Updating of Formulations, Constructive and Factor Validity and a Measure of Consent - N. A. Nikolaev; Yu. P. Skirdenko; A. A. Balabanova; A. V. Gorbenko; K. A. Andreev; M. M. Fedorin; M. A. Livzan; E. V. Chebanenko; G. M. Usov (Рациональная фармакотерапия в кардиологии)
Aim: To update the definitions of selected questions of the "QAA-25" (quantitative adherence assessment) scale and evaluate it according to the criteria of validity and measure of agreement.Materials and Methods. In a descriptive cross-sectional study including 200 patients with coronary heart disease, adherence was determined using traditional and alternative versions of selected questions of the QAA-25 scale, followed by assessment of construct validity, factor validity, and measure of agreement.Results. Alternative question versions did not significantly affect test results, with 81% of respondents in the outpatient sample and 69% in the inpatient sample rating them as "more acceptable." The QAA-25 scale has good construct and internal validity (α – 0.818, αst – 0.832), with moderate agreement (κ – 0.562) and demonstrates high reliability of internal validity – when scale items are consistently excluded, α values remain in the 0.801-0.839 range.Conclusion. The QAA-25 scale with modified question definitions should be used instead of the previous version of the scale. Good construct validity and factor validity, sufficient measure of agreement and specificity, high sensitivity and reliability of the QAA-25 scale allow to recommend it as a tool for assessing adherence to drug therapy, medical support, lifestyle modification and integral adherence to treatment in scientific and clinical practice.